Air pollution and cardiovascular disease hospitalization – Are associations modified by greenness, temperature and humidity?. (November 2021) - Klompmaker, Jochem O.; Hart, Jaime E.; James, Peter; Sabath, M. Benjamin; Wu, Xiao; Zanobetti, Antonella; Dominici, Francesca; Laden, Francine
Highlights: PM2.5 and NO2 were positively associated with CVD hospitalization. Ozone was only positively associated with CVD hospitalization at low exposure levels. Associations of PM2.5 were stronger with higher greenness. Associations of PM2.5 were stronger with lower temperature, specific humidity and Ox. Abstract: Background: Studies have observed associations between long-term air pollution and cardiovascular disease hospitalization. Little is known, however, about effect modification of these associations by greenness, temperature and humidity. Methods: We constructed an open cohort consisting of all fee-for-service Medicare beneficiaries, aged ≥ 65, living in the contiguous US from 2000 through 2016 ( 63 million individuals). We assigned annual average PM2.5, NO2 and ozone zip code concentrations. Cox-equivalent Poisson models were used to estimate associations with first cardiovascular disease (CVD), coronary heart disease (CHD) and cerebrovascular disease (CBV) hospitalization. Results: PM2.5 and NO2 were both positively associated with CVD, CHD and CBV hospitalization, after adjustment for potential confounders. Associations were substantially stronger at the lower end of the exposure distributions. For CVD hospitalization, the hazard ratio (HR) of PM2.5 was 1.041 (1.038, 1.045) per IQR increase (4.0 µg/m 3 ) in the full study population and 1.327 (1.305, 1.350) per IQR increase for a subgroup with annual exposures always below 10 µg/m 3 PM2.5 . Ozone was only positively associated with CVD, CHD and CBV hospitalization for the low-exposure subgroup (<40 ppb). Associations of PM2.5 were stronger in areas with higher greenness, lower ozone and Ox, lower summer and winter temperature and lower summer and winter specific humidity. Conclusion: PM2.5 and NO2 were positively associated with CVD, CHD and CBV hospitalization. Associations were more pronounced at low exposure levels. Associations of PM2.5 were stronger with higher greenness, lower ozone and Ox, lower temperature and lower specific humidity.